Monitoring of HIV-1 envelope-mediated membrane fusion using modified split green fluorescent proteins - Wang, Jianqi (J Virol Methods, 2009)
A simple, cell-based, membrane fusion assay system that uses split green fluorescent proteins (spGFPs) as an indicator was developed. The attachment of the pleckstrin homology (PH) domain to the N-termini of each spGFP not only localized the reporter signal to the plasma membrane but also helped the stable expression of the smaller spGFP of seventeen amino acid residues. It was shown that this system allowed real-time monitoring of membrane fusion by HIV-1 envelope protein (Env) without the addition of external substrates. This method can be adapted to the analyses of other viral membrane fusion.